A Shared Diagnostic Stewardship Approach to Autoimmune Encephalopathy Send-Out Testing. (28th October 2020) - Sharp, Cierra; Muluhngwi, Penn; Fletcher, Anita; Linder, Mark; Snyder, James; Jortani, Saeed
Abstract: As part of our laboratory testing utilization at University of Louisville Hospital (ULH), any send-out test ≥500 must be assessed by the clinical chemistry fellow or pathology resident for clinical necessity and as a way to provide consultation to the ordering physician on appropriate test utilization. In 2018, we noticed a prominent increase in the volume of panels for autoimmune encephalopathy (AE) and related disorders being ordered. This was met with considerable cost to the hospital, a lack of consensus on which panels should be ordered, and poor understanding of the clinical utility of these panels. These challenges presented an ideal project for our newly-formed diagnostic stewardship committee (DSC) at ULH. Through collaboration with the DSC, we were able to form a sub-committee with the Department of Neurology to develop an algorithm-based approach for ordering of these AE panels. Our goals were to improve diagnostic utility for the betterment of patient care, improve test utilization, and decrease cost associated with panel ordering. Prior to involvement of the DSC, we analyzed the number and cost of all AE panels ordered in 2018. We also calculated the number of positive panels and reviewed patient data to determine if a positive panel corresponded with a clinical outcome. After presenting our data to the DSC, an evidence-based approach was taken in collaboration with the Department of Neurology to develop an algorithm for AE test ordering. Results were analyzed for true positive rate, defined as a patient testing positive for an antibody with known etiology or association with AE based on result interpretation provided by Mayo Clinical Laboratories. The total cost of tests was also analyzed before implementation of the algorithm (January 1, 2019-July 31, 2019) and post-implementation (August 1, 2019-December 31, 2019). In 2018, 77 AE panels were ordered with an estimated charge to the laboratory of 137, 510. The true positive rate was 10%. Based on these test ordering patterns, we projected that 120 tests would be ordered in 2019, totaling >200, 000. Prior to the implementation of the algorithm in 2019, 55 tests were ordered, totaling 105, 210. Total true positive rate was 3.6%. After implementation of the algorithm, 23 tests were ordered, totaling 50, 220. The true positive rate was 13%. Using a shared diagnostic stewardship approach, we were able to develop an evidence-based algorithm for guiding physicians for AE panel ordering. Comparing test ordering patterns pre and post-implementation in 2019, our true positive rate more than tripled (3.6% to 13%), indicating that our algorithm was able to successfully identify the at-risk population for development of AE disorders. This was met with a >50% decrease in the number of tests ordered, and a total cost savings of 54, 990 compared to the first half of 2019.